Making innovation policy work learning from experimentation - Dutz, Mark A.; Kuznetsov, Yevgeny; Lasagabaster, Esperanza; Pilat, Dirk; Organisation for Economic Co-operation and Development (Paris OECD, 2014)
This book explores emerging topics in innovation policy for more inclusive and sustainable growth, building on concrete examples. It develops the notion of experimental innovation policy - which integrates monitoring and feedback at the policy design stage, and occurs continuously to improve impact and implementation. This approach should help improve the quality and efficiency of public expenditures supporting innovation policy. Experimental policy making is particularly important for new and emerging innovation domains, where the scope for learning and improvement is the greatest. To make the discussion as concrete and relevant as possible for practitioners and policy makers, three emerging domains of innovation policy are explored in greater detail: innovative entrepreneurship, green innovation, and pro-poor or base-of-the-pyramid (BoP) innovation.
Foreword -- Abbreviations and acronyms -- Executive summary -- Making innovation policy work: The benefits and lessons of experimental innovation policy -- New open economy industrial policy: Making choices without picking winners -- "Bottom of the pyramid" innovation and pro-poor growth -- Innovation for the "base of the pyramid" : Developing a framework for policy experimentation -- Incubating the incubation cycle : Two approaches to promoting techno-entrepreneurship in weak institutional environments -- Supporting affordable biotechnology innovations: Learning from global collaboration and local experience -- Fostering innovation for green growth: Learning from policy experimentation -- Making evaluations count: Toward more informed policy -- Scaling up and sustaining experimental innovation policies with limited resources : Peripheral Schumpeterian development agencies.
"This volume draws on the conclusions from the conference " Innovation Policy for Inclusive Growth", which took place in Rio de Janeiro in October 2011, and was co-hosted by the OECD, the World Bank Group and Brazil's National Development Bank"--Foreword.
Keywords: Technological innovations -- Economic aspects -- Congresses; Technological innovations -- Economic aspects